Sistemas de cálculo como formas de Logicismo - Ángel Nepomuceno Fernández (Crítica)
The logicism may be regarded like a fossil stone that has not utility nowadays. In this sense, logicism took care of the research about the foundations of mathematics but apparently its task arrived at its end many years ago because of sorne results that were eetablished during the century. However it is not wholly right. Understanding logicism as an attempt to reduce classical mathematics to logic means we can distinguish: 1) the idea according to which mathematic is logic in sorne way, and 2) a metaphysical program of research to: a) define mathematical notions as logical notions, and b) show that the mathematical theorems are logical theorems.